Soil-Climatic Zones of Haryana in Relation to the Cropping Patterns During The Rainy and Winter Seasons - Bishnoi, O P (Annals of Arid Zone, 2016)
Haryana State was demarcated into 1S homogenous soil-climatic zone during the rainy season by superimposing moisture index on the latest soil map. During the winter season, it was delineated into II soil-climatic zones during the drought year, 13soil-climatic zones during the normal years and 14 homogenous zones during above normal years by superimposing the moisture index, mean ,seasonal temperature index and mean seasonal temperature isopleths on the latest soil map. Due to wide variation in the accumulated soil moisture during the sub-normal and above normal years of rainfall, it was apparent to demarcate the Haryana State into homogeneous soil-climatic belts under the existing situations. The distribution of crops in these zones was made on the basis of the percentage of the area under the crop concerned to the total cropped area and efficient crops were also included in these zones.